Evidence-based recommendations for the rehabilitation and management of the ageing population with spinal cord injury: a systematic review of clinical practice guidelines (2024)
ABSTRACT: INTRODUCTION: The intersection of ageing and spinal cord injury (SCI) is of global concern. Two scenarios have been described: 1) “SCI withageing,” an increase in the average age of SCI onset, and 2) “ageing with SCI,” an increase in post-injury life expectancy. These scenarios entail complex health care and rehabilitation needs due to the accumulation of comorbidities, ageing-related and SCI-induced physiological changes, and post-SCI secondary health conditions. We systematically reviewed Clinical Practice Guidelines (CPGs) with the objective of identifying the extent to which SCI CPGs include recommendations for the rehabilitation and management of people who are “ageing with SCI” or who have acquired an “SCI with ageing”. We termed these as “ageing-related recommendations”. We also aimed to describe them and identify gaps. EVIDENCE ACQUISITION: We searched PubMed (NCBI), CINAHL Complete (EBSCOhost) and Embase (Elsevier) for relevant CPGs between 28 December 2022 and 5 January 2023. Included CPGs were evidence-based and had at least one ageing-related recommendation for SCI rehabilitation and management. We used the two core sets of the International Classification of Functioning, Disability and Health (ICF) to identify gaps. EVIDENCE SYNTHESIS: Only 16 (30%) of the 52 identified CPGs included ageing-related recommendations. Most were recent US or European publications and lacked specific chapters on ageing. These CPGs included 40 ageing-related recommendations, mostly “strong” but based on “low” to “very low” quality of evidence. The overall quality of the development process was low and did not consider the values and preferences of stakeholders and patients. Common topics included cardiovascular, bone, metabolic, bowel, bladder, and skin health. The recommendations could be linked to 30 ICF categories which represented only 18% of the ICF categories included in the comprehensive versions of two ICF Core Sets. Key gaps were found in mobility, interpersonal interactions, and relationships, neuromusculoskeletal and movement-related, mental, sensory and pain functions. CONCLUSIONS: There is a notable lack of high-quality ageing-related recommendations for SCI management and rehabilitation. Future research should prioritize the generation of high-quality evidence to develop age-sensitive CPGs. Future SCI CPGs need to address the complex challenges at the interface of ageing and SCI, considering patient and stakeholder preferences. (Cite this article as: Seijas V, Schrepfer L, Posada AM, Spir MA, Machado B, Sigrist-Nix D, et al. Evidence-based recommendations for the rehabilitation and management of the ageing population with spinal cord injury: a systematic review of clinical practice guidelines. Eur J Phys Rehabil Med 2024;60:433-44. DOI: 10.23736/S1973-9087.24.08244-3) Key words: Spinal cord injuries; Aging; Practice guideline